Factors influencing stem cell donation in post-pandemic Italy among healthcare professionals and the general population: A multicentre study using statistics and generative artificial intelligence - Rubbi, Ivan; Lupo, Roberto; Botti, Stefano; Grasselli, Stefania; Ayoubi, Amer; Ianne, Chiara; Antonazzo, Marcello; Caldararo, Cosimo; Vitale, Elsa; Cannici, Chiara; Cioce, Marco; De Cecco, Valentina; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The general Italian population’s knowledge regarding stem cells is a complex topic, laden with uncertainty and inconsistency. The decision to become a donor can be influenced by factors such as age, education, occupation, sex, ethnicity, and religion. Healthcare professionals’ knowledge guides both patients and the practices and techniques they themselves implement. This study aimed to compare the level of knowledge among healthcare professionals and non-healthcare workers regarding hematopoietic stem cell donation in the post-pandemic period. Methods: The data used for this study were extracted from the database of a previous published survey that involved healthy adult responders.Results: A total of 1,054 individuals participated in the study. Among them, 44.8% (n = 472) were healthcare professionals, and 78.8% (n = 831) reported no prior experience with stem cell transplantation. The study examined differences in knowledge about the bone marrow donor registry between healthcare and non-healthcare participants, revealing that the former demonstrated significantly higher levels of knowledge (over 60%, with R = 64.8–90.2). However, only about 21% of the overall sample reported being registered in the donor registry, with similar proportions observed between the two groups (p = 0.773). The motivations for registration included altruism, access to information,[...]. Empathy was found to be significantly more pronounced among healthcare professionals, while satisfaction was higher among non-healthcare participants. A significant number of positive correlations were observed between feelings of solidarity and gratification and other positive emotions, as well as significant negative correlations with items reflecting negative feelings.Conclusions: There is no a single aspect that influences stem cell donation but rather multiple elements, from inherent characteristics such as sex to social, religious and personal aspects. Healthcare professionals have more knowledge about stem cell donation, but the feelings and beliefs they express may be similar to those of the general population.